2020
DOI: 10.1177/0021998320934860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano Al2O3 coated Ag reinforced Cu matrix nanocomposites on mechanical and tribological behavior synthesis by P/M technique

Abstract: In this study, copper powder was reinforced with different weight percentages of Al2O3 particles (0, 5, 10, and 15 wt.% Al2O3 coated Ag) to produce Cu-Al2O3 composites by mechanical alloying and uniaxial cold pressing/sintering route. Electro-less deposition was used to coat Al2O3 particles with Ag. The microstructure of the consolidated samples was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) elemental mapping. The porosity, microha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…16,17 Since then, academics have worked to better understand the procedure and have begun to develop it by examining the impact of the ARB parameters involved, performing hot ARB, using it on a variety of metals and reinforcement particles, creating multilayered composites, and evaluating their mechanical and microstructural characteristics, texture, and other characteristics. [18][19][20][21] Several Al-based composites, including Al/SiC, 22 Al/Al 2 O 3 , 23 Al/TiO 2 , 24,25 Al/SiO 2 , 26 Al/W, 27 and Al/WC, 28 have been produced using the ARB approach. The use of severe plastic deformation, which refines the grains and hence enhances the strength in accordance with the hall-Petch relation without affecting the sample's size, is the main procedure in ARB.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Since then, academics have worked to better understand the procedure and have begun to develop it by examining the impact of the ARB parameters involved, performing hot ARB, using it on a variety of metals and reinforcement particles, creating multilayered composites, and evaluating their mechanical and microstructural characteristics, texture, and other characteristics. [18][19][20][21] Several Al-based composites, including Al/SiC, 22 Al/Al 2 O 3 , 23 Al/TiO 2 , 24,25 Al/SiO 2 , 26 Al/W, 27 and Al/WC, 28 have been produced using the ARB approach. The use of severe plastic deformation, which refines the grains and hence enhances the strength in accordance with the hall-Petch relation without affecting the sample's size, is the main procedure in ARB.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] It is generally known that adding graphite, a solid lubricant, to the copper matrix can enhance metals' wear and friction characteristics. 9,10 Venkatesh and Vaddi Seshagiri 11 produced copper matrix composite materials by adding Al 2 O 3 and Gr to copper and investigated its wear and corrosion behavior. Their results indicated that the corrosion resistance of the nano and micro-reinforced composites was improved and the weight loss was minimized by increasing the content of graphite in the composite.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, copper matrix composites (CMCs) with ceramic reinforcements have been widely studied to achieve good electrical and thermal conductivity and increase hardness and wear resistance [9][10][11][12]. Composites can be used in relays and switches, electrical discharge machining electrodes, ignition pens, and other similar items [13].…”
Section: Introductionmentioning
confidence: 99%